PENGARUH KOMPETENSI HUMAN CAPITAL DAN DISIPLIN KERJA TERHADAP KINERJA ASN PADA DINAS PERDAGANGAN SULAWESI SELATAN - Utami, Rozachita Amalia; Nuhung, Mahmud (COMPETITIVENESS, 2018)
This study aims to determine and analyze the influence of Human Capital Competence and Work Discipline on the performance of employees of the South Sulawesi Province Trade Office. The design used in this research is a descriptive survey method with regression techniques. The population in this study were 68 employees as many as 68 people. Data collection techniques used in this study were questionnaires and surveys.The results of this study indicate that. Competence has a significant positive effect on employee performance with P = 0.028 <0.05 with a coefficient value of 0.196, this coefficient indicates that the better the competence of employees at the South Sulawesi Provincial Trade Office, the better. Work discipline has a significant positive effect on employee performance with P = 0.022 <0.05 with a coefficient value of 0.263, this coefficient indicates that the higher the employee's work discipline, the performance will also increase. Work discipline is very influential on employee performance, because the success of an organization and achieving organizational goals is determined by employee performance. Keywords: Competence, Work Discipline and Performance.